2002
DOI: 10.1080/00224490209552131
|View full text |Cite
|
Sign up to set email alerts
|

The sexual inhibition (SIS) and sexual excitation (SES) scales: II. Predicting psychophysiological response patterns

Abstract: This study evaluated the predictive value of a newly developed measure of the propensity for sexual inhibition and excitation; the Sexual Inhibition Sexual Excitation Scales (SIS/SES). Sexual, cardiovascular, and startle responses were measured in a group of 40 sexually functional men during the presentation of threatening and nonthreatening erotic films. Two levels of performance demand were created and two films were combined with a distraction task. Participants were assigned to high and low groups for each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
87
4
15

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 133 publications
(115 citation statements)
references
References 16 publications
7
87
4
15
Order By: Relevance
“…Examples of general, nonsexual traits that have been studied and found relevant to the prediction of risky sexual behavior (e.g., number of sexual partners, consistency in using condoms) are sensation seeking, impulsivity, and harm avoidance (Bancroft et al, 2003(Bancroft et al, , 2004Gil, 2005;Hoyle et al, 2000;Lejueza, Bornovalovaa, Daughtersa, & Curtin, 2005), Examples of sexuality-related traits that have been found to be associated with risky sexual behavior are erotophilia (e.g., Fisher & Fisher, 1999) and the propensity for sexual inhibition (Bancroft et al, 2003(Bancroft et al, , 2004, as measured by the Sociosexual Orientation Survey (SOS) and the Sexual Inhibition/Sexual Excitation scales (SIS/SES), respectively. Interestingly, both measures have been found to be predictive of sexual responses in the laboratory (e.g., Janssen, Vorst, Finn, & Bancroft, 2002b;Janssen & Bancroft, 2007;Fisher, Byrne, White, & Kelley, 1988), which further supports the relevance of considering not just the role of (general and sexual) personality factors in risky sexual behavior, but also their possible psychophysiological correlates.…”
Section: Introductionmentioning
confidence: 71%
“…Examples of general, nonsexual traits that have been studied and found relevant to the prediction of risky sexual behavior (e.g., number of sexual partners, consistency in using condoms) are sensation seeking, impulsivity, and harm avoidance (Bancroft et al, 2003(Bancroft et al, , 2004Gil, 2005;Hoyle et al, 2000;Lejueza, Bornovalovaa, Daughtersa, & Curtin, 2005), Examples of sexuality-related traits that have been found to be associated with risky sexual behavior are erotophilia (e.g., Fisher & Fisher, 1999) and the propensity for sexual inhibition (Bancroft et al, 2003(Bancroft et al, , 2004, as measured by the Sociosexual Orientation Survey (SOS) and the Sexual Inhibition/Sexual Excitation scales (SIS/SES), respectively. Interestingly, both measures have been found to be predictive of sexual responses in the laboratory (e.g., Janssen, Vorst, Finn, & Bancroft, 2002b;Janssen & Bancroft, 2007;Fisher, Byrne, White, & Kelley, 1988), which further supports the relevance of considering not just the role of (general and sexual) personality factors in risky sexual behavior, but also their possible psychophysiological correlates.…”
Section: Introductionmentioning
confidence: 71%
“…Incorporating social norms, courtship and relationship duration, recovery from infection, attachment, and other social influences on sexual risk will increase the predictive value of the model. Also, future studies could include morevariablesrelevanttosexualexcitationandinhibition.Forexample,forthesakeofsimplicity,thecurrentmodelonlyusedonetype of inhibition, while research in men and women has revealed that atleasttwotypesofinhibitionmayexist(e.g., Graham,Sanders,& Milhausen, 2006;Janssen, Vorst, Finn, & Bancroft, 2002a, 2002b. Future models could also incorporate mate value detection mechanisms and assortative mating functions, distributing more partners and other resourcestoagentsofhighmatevalue.As a sort of intragenerational genetic algorithm, learning is a crucial element of an ABM of human motivation (Savage, 2000) which obviously also has an important role in human sexuality.…”
Section: More Complex Modelsmentioning
confidence: 97%
“…The primary personality variable incorporated in the current investigation was the propensity for sexual inhibition and sexual excitation, assessed by the Sexual Excitation/Sexual Inhibition Scale (SES/SIS) (Carpenter et al, 2008;Janssen et al, 2002b). This 45-item questionnaire measures three factors: (1) the propensity for sexual excitation (SES), (2) the propensity for sexual inhibition due to performance failure (SIS1), and (3) the propensity for sexual inhibition due to performance consequences (SIS2).…”
Section: Personality Related Variablesmentioning
confidence: 99%